2019
DOI: 10.1002/cne.24748
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine hydroxylase immunolabeling reveals the distribution of catecholaminergic neurons in the central nervous systems of the spiders Hogna lenta (Araneae: Lycosidae) and Phidippus regius (Araneae: Salticidae)

Abstract: With over 48,000 species currently described, spiders (Arthropoda: Chelicerata: Araneae) comprise one of the most diverse groups of animals on our planet, and exhibit an equally wide array of fascinating behaviors. Studies of central nervous systems (CNSs) in spiders, however, are relatively sparse, and no reports have yet characterized catecholaminergic (dopamine [DA]‐ or norepinephrine‐synthesizing) neurons in any spider species. Because these neuromodulators are especially important for sensory and motor pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 113 publications
0
4
0
Order By: Relevance
“…This distinct set of catecholaminergic neurons underpins the relay of visual information from the VN to the AB already deduced by the presence of the connecting tract. Interestingly, in euchelicerates, a recent study of TH immunoreactivity in the brain of spiders has revealed a similarly extensive labeling for catecholamines in the VNs and several AB layers [ 70 ]. Further, histofluorescent visualization of catecholamines in the brain of xiphosurans has also indicated their presence in neurites of the AB and some VNs [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This distinct set of catecholaminergic neurons underpins the relay of visual information from the VN to the AB already deduced by the presence of the connecting tract. Interestingly, in euchelicerates, a recent study of TH immunoreactivity in the brain of spiders has revealed a similarly extensive labeling for catecholamines in the VNs and several AB layers [ 70 ]. Further, histofluorescent visualization of catecholamines in the brain of xiphosurans has also indicated their presence in neurites of the AB and some VNs [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tyrosine hydroxylase (TH) is the rate-limiting enzyme in the synthesis of catecholamines (dopamine, adrenaline, noradrenaline) [ 69 ], of which dopamine represents an important neurotransmitter in the arthropod nervous system. A monoclonal mouse antibody raised against purified TH from rat PC12 cells was used, having been prior to this study successfully applied in spiders [ 70 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The unique structural characteristics related to web building, such as silk and mechanosensory sensilla, have garnered increased interest and detailed descriptions. However, only a small number of molecules (for example, neuropeptide) or neurons had been thoroughly described in spiders 49 . We found that most PSGs were highly expressed on the brain, indicating the key role of CNS in the evolution of spiders beyond the structure innovations.…”
Section: Mushroom Body Evolution In Web-building Spidersmentioning
confidence: 99%